Metal–organic frameworks loaded Au nanozymes with enhanced peroxidase-like activity for multi-targeted biodetection. Issue 23 (11th October 2022) - Liu, Quan; Wang, Hanhan; Yang, Qi; Tong, Yuping; He, Weiwei
Abstract : Benefiting from the enhanced POD-like activity of Au/UiO-66, multi-target detection of glucose, dopamine and sulfide ion was realized based on a distinct mechanism. Abstract : Size and surface effects definitely play an important role in promoting the enzyme-like catalytic activity of metal nanozymes. However, monodisperse small-size nanozymes require surface modification to avoid agglomeration, which largely limits their catalytic activity. In this work, a zirconium-based metal organic framework (UiO-66) with high chemical stability and porosity was applied as a carrier, on which uniform Au nanoparticles (NPs) were successfully loaded, forming Au/UiO-66 nanocomposites. Benefiting from the naked and active surface of the distributed Au NPs, Au/UiO-66 exhibited prominently enhanced peroxidase activity as well as good performance and stability. Inspired by the significant peroxidase activity of Au/UiO-66 and the distinct inhibitory effect of biological substances on peroxidase activity, a multi-targeted analytical platform was designed and established. The results proved that the developed platform realized accurate and effective detection for glucose, dopamine and HS − with a limit of detection (LOD) of 0.033 mM, 0.0022 mM and 0.0016 mM, respectively.